From Pandemic to Pedagogy: Teaching the Technology of Lawyering in Law Clinics - Sarah R. Bonnin; Luz E. Herrara (Washington University Journal of Law and Policy, 2022)
The COVID-19 pandemic has transformed the nation’s approach to work and learning. Law schools, law firms, courts, and administrative agencies abruptly closed their offices and quickly reimagined how to perform their daily functions remotely. Many of these institutions have plans to maintain aspects of remote operations and services post-pandemic. With this in mind, the authors of this Article conducted a survey of law school clinical faculty during the winter of 2021 to better understand how clinicians pivoted their instruction and practice using technology during the pandemic. The authors use the survey results to show how the COVID-19 experience positions clinical programs to be leaders in answering the growing calls to incorporate technical competency into legal education. The authors draw on the experiences of clinicians during the pandemic to demonstrate how law practice technology can be deliberately and thoughtfully integrated into existing clinical pedagogy and practice. The Article concludes by urging clinicians to build on the current momentum to embrace what they call “the technology of lawyering” as an indispensable component of clinical education.
Keywords: Remote learning; Remote work; Technical Competency in Legal Education; Legal Clinicians; Clinical Education